The Influence of Atmospheric Circulation on Mean and Extreme Weather Conditions on Kaffiøyra (NW Spitsbergen, Svalbard Archipelago) in the Summer Seasons 1975–2015 - Araźny, Andrzej; Przybylak, Rajmund; Kejna, Marek (Frontiers in Environmental Science, 2022)
The paper presents results describing the influence of Atmospheric Circulation (AC) on meteorological conditions on Kaffiøyra (NW Spitsbergen, Svalbard Archipelago) in 23 summer seasons (Jul 21–Aug 31) in the years 1975, 1977–80, 1982, 1985, 1989, 1997–2000, 2005–15. The analysis covered the diurnal sums or means of major meteorological parameters: total cloudiness, sunshine duration, air temperature, wind speed, relative air humidity, water vapour pressure, and precipitation. Extreme weather events in terms of any given parameter were defined as days whose diurnal values (mean/sum) were in the ≤5th or ≥95th percentiles. The influence of AC on meteorological conditions on Kaffiøyra was analysed using the calendar of circulation types (CT) by T. Niedźwiedź (2018). In the study area, the variability of individual meteorological parameters depends primarily on air-mass advection direction, while type of baric regime is less important. Our study highlights that the greatest positive anomalies and a significant frequency of extreme values of cloudiness, wind speed, air temperature, humidity and precipitation occurred during air mass advection mainly from the SW and S. It was also demonstrated that sunshine duration correlated statistically significantly with the frequency of the anticyclonic macrotype, and precipitation with the cyclonic macrotype. The results confirmed that atmospheric circulation plays the most important role in shaping weather conditions in Spitsbergen.